Enhanced mechanical and electromagnetic properties of polymer composite with 2.5D novel carbon/quartz fiber core-spun yarn woven fabric. (July 2021) - Yuan, Linjia; Fan, Wei; Miao, Yaping; Li, Juanzi; Xue, Lili; Dang, Wensheng; Dong, Jingjing; Wei, Liang; Sun, Runjun
A set of radar absorbent carbon/quartz fiber hybrid core-spun yarns (9B, 12B17A, and 12B25A) with different braided structure (round and flat) and braiding angle (17° and 25°) were designed, and then the mechanical and electromagnetic properties of the corresponding 2.5D core-spun yarn/epoxy composites (9BC, 12B17AC, and 12B25AC) were investigated in this study. The results showed that the composite made by round core-spun yarns with large braiding angle (12B25AC) had the highest mechanical properties and the best radar absorbing properties in the three types of 2.5D core-spun yarn/epoxy composites. The effective absorption bandwidth (reflection loss < −10 dB), maximum reflection loss value, tensile strength, and bending strength of the 12B25AC was 3.9 GHz (14.1–18 GHz), −17.2 dB at 16.7 GHz, 428.43 MPa, and 545.10 MPa, respectively. Therefore, the 2.5D reinforced composite by the round core-spun yarns with large braiding angle offers a unique architectural method to attain both outstanding radar absorption and mechanical performances.